A 1400-years flood frequency reconstruction for the Basque country (N Spain): Integrating geological, historical and instrumental datasets. (15th June 2021) - Corella, J.P.; Benito, G.; Monteoliva, A.P.; Sigro, J.; Calle, M.; Valero-Garcés, B.L.; Stefanova, V.; Rico, E.; Favre, A.-C.; Wilhelm, B.
Abstract: We present the first reconstruction of past flood events variability in the Basque Country and Western Ebro Basin (Northern Spain) integrating instrumental hydrological datasets (last 20 years), documentary archives (last 700 years) and Lake Arreo (655 m a.s.l.) sedimentary paleoflood record (last 1400 years). In this lake, allochthonous coarse and fine detrital layers (CDL and FDL respectively) intercalated within endogenic laminites were identified and interpreted as high- and moderate-energy flood events. The interplay between human activities and hydroclimate variability has controlled the deposition of these flood layers. Gauged data for the last 20 years suggest that floods are typically generated by heavy rainfall events on saturated soils after several days of continuous rainfall. These events occur mostly during the cold season (Oct–May). The reconstructed frequency of high-magnitude flood events from the lake record is coherent with the historical cold-season floods from Basque rivers. The lowest flood frequency took place during the 6–7 th and 10–15 th centuries, while higher flood frequency occurred during the 8–9 th centuries and the last 500 years. Fluvial and lacustrine paleoflood records and documentary evidence show abrupt and large increases in extreme flood frequency during the termination of the Little Ice Age (1830–1870 CE) and mid to late 20 th century, both periods of Rapid Climate Change (RCC). The significant increase in flood frequency observed during RCC suggests that a similar pattern could be expected in the near future with the ongoing global warming. Highlights: First multi-proxy flood reconstruction in Northern Spain covering 1400 years. Integration of instrumental, historical and geological records provides a regional, high-resolution flood archive. Higher flood frequency during periods of Rapid Climate Change (RCC).